Treatment Cost of COVID-19 in Hospitals affiliated to Kashan University of Medical Sciences: Time-Driven Activity-Based Costing - Meghdad Rahati; Esmaeil Fakharian; Ali Yousefianarani; Aydine Omidvar; Zahra Nazemi-bidgoli (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2021)
Background: Due to limited resources, efficiency is very important to maximize resources for hospitals. Time-Driven Activity-Based Costing estimates costs and provides valuable information to increase efficiency. Therefore, the cost of COVID-19 in the hospitals affiliated with Kashan University of Medical Sciences was investigated using this method. Method: In this cross-sectional and retrospective study, the statistical population included all patients (n = 3129) with COVID-19 hospitalized in the Seyed Al-Shohada hospital (88 beds) and Shagid Beheshti hospital (700 beds) selected via census method during March and April 2020. Data collection was conducted through review of litreture (library method field); and review of accounting documents, direct observation of activities related to the treatment of patients, interviews with top managers for timing of receiving services by patients (field method). The descriptive statistics including means and frequency tables was reported and time-driven activity-based costing was conducted. Data analyses were performed using Excel software. Results: Findings showed that the cost of one bed night for COVID19 patients was 22,866,669 Rials in Shahid Beheshti hospital and 30,554,405 Rials in Seyed Al-Shohada hospital and was 23,672,447 Rials for both hospitals in total. The cost of treatment of COVID19 by time-driving costing method was higher than the tariff approved by the Supreme Insurance Council. Conclusion: Due to the difference between the cost of treatment of COVID-19 and the tariffs, it is necessary to calculate the bed night of these patients based on the tariffs of special wards. Moreover, due to the high cost of these patients, it is necessary to make appropriate policies for allocating beds in the hospitals affiliated to the University of Medical Sciences.